A Communist in the Council Chambers: Communist Municipal Politics, Ethnicity, and the Career of William Kolisnyk - Epp, Stefan (Labour / Le Travail, 2009)
Abstract The election of William Kolisnyk as alderman for Winnipeg’s Ward Three in the fall of 1926 was celebrated as one of the first times that any candidate in North America running under the banner of a Communist Party was elected to public office. Although he was only an alderman for four years, a study of Kolisnyk’s political life contributes to the study of communist history in several ways. His term in office was split roughly in half by the introduction of Third Period ideology. As the Communist Party’s sole elected representative at the time, Kolisnyk’s political activity demonstrates the practical implications of this dramatic policy shift. While the Third Period radically changed Kolisnyk’s politics, several local issues significantly influenced his politics. Ethnicity, both within the Party and in Kolisnyk’s constituency, profoundly aﬀected his career. The paper also examines the political issues pursued by communists at the municipal level and the communist community that brought Kolisnyk to office. Therefore, this examination of William Kolisnyk’s aldermanic career reveals the importance of international influences as well as the political realities of Winnipeg’s communist community, both of which contributed to the political activities of one of Canada’s first elected communists.